2014
DOI: 10.3390/ijerph110404356
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, Perceived Side Effects and Benefits of Electronic Cigarette Use: A Worldwide Survey of More than 19,000 Consumers

Abstract: Background: Electronic cigarette (EC) use has grown exponentially over the past few years. The purpose of this survey was to assess the characteristics and experiences of a large sample of EC users and examine the differences between those who partially and completely substituted smoking with EC use. Methods: A questionnaire was prepared, translated into 10 different languages and uploaded in an online survey tool. EC users were asked to participate irrespective of their current smoking status. Participants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

58
336
7
12

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 334 publications
(413 citation statements)
references
References 25 publications
58
336
7
12
Order By: Relevance
“…In a fourth, the EC test products were provided by an EC company [57], and in a fifth, authors reported having received previous funding from EC companies [50]. One study was sponsored by an EC user advocate group [61] and another by the Italian antismoking league [58]. The remaining six studies were government or university sponsored [51,52,54,55,60] or did not report funding [49].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a fourth, the EC test products were provided by an EC company [57], and in a fifth, authors reported having received previous funding from EC companies [50]. One study was sponsored by an EC user advocate group [61] and another by the Italian antismoking league [58]. The remaining six studies were government or university sponsored [51,52,54,55,60] or did not report funding [49].…”
Section: Discussionmentioning
confidence: 99%
“…Only two of the studies on EC safety reported results by sex [55,56], so we were not able to determine whether EC exposure affected males and females differently. In six of the studies, authors did not standardize EC dosage across the study sample [49,54,[57][58][59][60]; in three, no comparison group was included [51,54,57]; and in one, neither exposures nor outcomes were validated [61].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations